Voices cast out to talk us in : poems - Roberson, Ed (Iowa poetry prize., 1995)
There is no one else like Ed Roberson - certainly there is no other poet like him. His is an oblique, eccentric, totally fascinating talent. Because of these qualities, it may seem that he is difficult to follow - as Ornette Coleman or Gabriel García Márquez or Romare Beardon seems difficult to track at times. But his strength of vision is always evident; the quickness and inclusiveness of his voice can sweep a reader along into new and refreshing areas. Roberson's poetic moves are not tricks or affected traits. They are artistic and deeply considered techniques. Re.